Teachers’ Advancement and Retention as Correlates of Students’ Academic Performance in Ogun State Public Secondary Schools - Sheyin, Adejoke Olabisi; Adeniran, Semiu A. (NIU Journal of Humanities, 2019)
This study was carried out to investigate the correlation among teachers’ advancement, teachers’ retention and students’ academic performance in Ogun State Public Secondary Schools. Descriptive survey research design was used while fifteen (15) secondary schools were randomly selected from the One hundred and forty- two (142) in Ogun central senatorial district of ogun state. Also, four hundred and ninety eight teachers were selected from the chosen schools. Questionnaire tagged: ‘Teachers’ advancement and retention questionnaire’ (TARQ) was used to collect data for the study. Also, Senior Secondary School Students’ WAEC results from 2013 to 2015 was used to establish the performance of the students while Pearson product moment correlation (PPMC) and multiple regression analysis were used to establish the correlates among teachers’ advancement, teachers’ retention and students’ academic performance in Ogun state Public Secondary Schools. The result shows that there are significant correlates among teachers’ advancement, teachers’ retention and students’ academic performance in Ogun state public secondary schools. Teachers’ advancement also aids teachers’ quality, commitment and retention which in turn influence students’ academic performance. It was recommended among other things that: teachers’ advancement should be fully implemented to accommodate and sustain compulsory in-service training in form of enrollment for cluster meeting and regular promotion to enhance teachers’ status and full blown professionalization of teaching profession. Also, there should be a deliberate attempt to address teachers’ motivation crisis through introduction of teachers salary structure (TSS) and reduction of daily workload of teachers so that the best brains would be attracted into the profession and those in service would choose to stay thereby reducing high turnover rate of good teachers. Since one cannot give what he does not have, only qualified teachers should be employed to teach and they should be given necessary tools and provided with conducive environment to keep them on the job in order to achieve enhanced students’ academic performance that we are all yearning for. Key words : teachers’ advancement, teachers’ retention, correlates, motivation, academic performance